Keterkaitan Gaya Hidup Terhadap Gangguan Sistem Gerak (Tremor) pada Guru SD Negeri 4 Citeras - Savira Hidayanti; Tahri Tahri; Patwa Nurmakah; Juhaeriyah Juhaeriyah; Asih Nuryati (Jurnal Biologi dan Pembelajarannya (JB&P), 2023)
Health is an important thing for human life, including the health of the human movement system. Some people think that disorders or diseases of the locomotor can occur in people who are elderly or elderly. However, nowadays many people their productive age and even teenagers experience disorders or diseases of their moving organs. The problem that often occurs in the movement system is tremors in the hands which can occur at both old and young ages. This study aims to examine the relationship between lifestyle and movement system disorders (tremors) using qualitative methods through interviews, observation, and documentation in data collection. Based on the results obtained, 16.7% of respondents had experienced tremors. And then 83.3% of respondents stated that they experienced muscle pain. This is in line with the response of more than 80% stating that they often do heavy work and consume caffeine.